3PL selection criteria in integrated circuit manufacturing industry in Taiwan. Issue 1 (11th January 2016) - Hwang, Bang-Ning; Chen, Tsai-Ti; Lin, James T.
Abstract : Purpose: – The purpose of this study was to identify the key third-party logistics (3PL) selection criteria for the integrated circuit (IC) manufacturing industry in Taiwan. The IC manufacturing industry seeks global sourcing, and is facing increasing pressure due to fierce market competition. More than a cost reduction strategy, 3PL is a strategic tool for IC manufacturers to gain a competitive advantage in a global supply chain complex. Design/methodology/approach: – The triangulation method that combines qualitative and quantitative approaches was used in the study. The qualitative approach of focus group discussions was adopted to establish the decision framework, and the quantitative approach of the analytic hierarchy process was used to explore the relative importance of the 3PL selection criteria. Finally, an in-depth proof-by-example interview was undertaken to provide an insightful interpretation of the research results. Findings: – The research shows that performance is the most important criterion group, followed by cost, service, quality assurance, intangible and information technology. At the detailed sub-criteria level, document accuracy, problem-solving capability, continuous cost reduction, value-added services and associated cost control capability are the top five criteria. Research limitations/implications: – This study focused on the IC manufacturing sector in Taiwan. Multi-country and multi-industry studies are recommended to help further validate and generalise the research findings. Originality/value: – Due to its application of triangulation, this study is a pioneering work on the 3PL selection criteria in a high-tech manufacturing industry. Furthermore, the value of this research is that it enhances the body of knowledge of 3PL selection by identifying certain emerging selection criteria, it could serve as a guideline for IC manufacturers in planning logistics outsourcing actions and it could significantly contribute to the efforts of 3PL providers in evaluating whether they comply with customer needs and adhere to core competency development.